Fiscal Inequality Analysis in the Province of Aceh (Year 2010-2019) - Vina Ananda; Arina Jannati Alfina (International Journal of Business and Applied Economics, 2023)
This study aims to determine the level of fiscal inequality in districts in Aceh Province and the causes of fiscal inequality in districts in Aceh Province. The data used in this study is time series data in the form of data on the  population and GRDP of districts and cities in Aceh Province. The data analysis method used in this research is descriptive qualitative analysis to describe the level of inequality in Aceh province based on the Williams Index. From the data analysis, it is known that for the 2016–2020 period, the district or city that has the lowest inequality is Aceh Besar, where the average Williamson Index is 0.3048. Since the 2016–2020 period, the district or city that has had the highest level of inequality is the Pidie district, where the average Williamson Index is 0.5511. Overall, the lowest fiscal inequality in Aceh Province occurred in 2018, where the Aceh Williamson Index in 2013 was 0.3279. Overall, the highest fiscal inequality in Aceh Province occurred in 2017, when the Aceh Williamson Index was 0.4338.